Identification and quantification of termms in upland rice roots - Czapak, Cecília; Ferreira, Evane; Nogueira, Sebastião B. (Pesquisa Agropecuaria Brasileira, 1993)
The population of termites in roots of Araguaia and Guarani varieties was identified and quantified. Twelve genera of Termitidae and one, Heterotermes, of Rhinotermitidae were found. The number of specimens collected in each genus gave the following decreasing order of importance: Anoplotermes, Grigiotermes, Heterotermes, Aparatermes, Procornitermes, Syntermes, Ruptitermes, Dihoplotermes, Labiotermes, Embiratermes, Neocapritermes, Cornitermes e Cornicapritermes. The first five genera were characterized as upland rice pests and Anoplotermes, Grigiotermes, Aparatermes were identified for the first time.